Variant in CD209 promoter is associated with severity of liver disease in chronic hepatitis C virus infection - Stevenson, Nigel; O'Farrelly, Cliona (My University, 2010)
CD209, a c-type lectin expressed by dendritic cells (DCs), acts as a pathogen recognition receptor. A single nucleotidepolymorphism (SNP) in the promoter region of CD209(-336A/G;rs4804803) affects transcription and is associated with the severity of tuberculosis and dengue fever. Because CD209 binds hepatitis C virus(HCV) glycoprotein-E2, we investigated this SNP in the context of chronic HCV infection. A total of 131 Irish women who had received HCV-contaminated anti–D-immunoglobulin and 79 healthy control subjects were genotyped. We found no association between rs4804803 and the risk of HCV chronicity. However, of those with chronic infection, possession of at least oneg-allele was associated with more advanced liver disease,with significantly higher liver fibrosis scores and levels of alanine transaminase (ALT) observed. We conclude that rs4804803, an SNP in theCD209 promoter, contributes to severity of liver disease in chronic HCV infection.
PUBLISHED
Keywords: CD209; DC-SIGN; Hepatitis C virus; Chronic viral infection; Single-nucleotide polymorphism; Immunology, Inflammation & Infection